ANALISIS PELAKSANAAN EVALUASI PEMBELAJARAN OLEH GURU DI SMA NEGERI 1 KECAMATAN KUBU KABUPATEN ROKAN HILIR - Mira Ulfa Joza; Caska Caska; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTSMA Negeri 1 sub-district is the stronghold of one of the schools that are inRokan Hilir . To determine the success learning conducted in an educationalinstitution would require evaluation . The existence of an evaluation is deemedimportant in education . The purpose of the study was to determine the evaluationof learning by the teacher in SMA Negeri 1 Kubu Sub Rokan Hilir . Thepopulation in this study was the teacher of SMA Negeri 1 Rokan Hilir Subdistrictfaction consisting of thirty- six ( 36 ) teachers with sampling using a samplingtechnique that is saturated sampling technique used when all members of thepopulation as a sample . The technique of collecting data using questionnairesand documentation . techniques of data analysis using descriptive methods . Theresults showed that the evaluation of learning by the teacher in SMA Negeri 1Kubu Sub Rokan Hilir 52.78% teachers in the criteria of